Predicting factors affecting green purchase intentions towards green products. (18th June 2021) - Jain, Vijay Kumar; Dahiya, Aditi; Tyagi, Vikas; Dube, Praveen
The growing consumption of goods and services across the world has caused depletion of natural resources and severe damage to the environment. The repercussions of this damage are reflected in the form of global warming, increased environmental pollution and decline in flora fauna (Chen and Chai, 2010). Due to growing scarcity of natural resources and rise in global temperature, green consumer behaviour has occupied an important role in promoting environmental awareness and reducing per capita greenhouse emissions. The current paper aims to identify the factors affecting consumer green purchase intention. It further tests the impact of purchase intention on purchase behaviour. Self-structured questionnaire was administered to get the respondent's opinions towards factors affecting purchase intention for green products. Structural equation modelling has been used to test the propounded hypotheses. All hypotheses except one, have been found statistically significant. The findings of the study would help marketers and policy makers to plan strategies for promoting green consumption among consumers, thereby, saving precious resources and improving environmental performance.